Influence of Timing of Basal Fertilizer Application on Growth and Yield of Maize (Zea mays L.) in the Guinea Savannah Agroecology of Ghana : Influence of Timing of Basal Fertilizer Application on Growth and Yield of Maize (Zea mays L.) - Alhassan Bawa; Mansuru Salifu; Abdul Fatawu Yakubu; Fuseini Jibreel (Asia Pacific Network for Sustainable Agriculture, Food and Energy Network (SAFE Network), 2026)
The time of basal fertilizer application in maize production influences the economic and biological yield of the maize crop in the sub-Saharan region and Ghana in particular. Therefore, inappropriate timing of basal fertilizer application in maize production is one of the major factors that reduces maize yield. Field experiments were conducted at the Tamale Technical University experimental field during the 2024 and 2025 cropping seasons from August to November each year to evaluate the effect of time of basal fertilizer application on the growth and yield of maize. The experiment was arranged in a Randomized Complete Block Design with three treatments and three replications. Data were collected on growth and yield parameters. The data were analyzed using analysis of variance, and treatment means were compared using the least significant difference test at a 5 % probability level. The results showed that timing of basal fertilizer application had a significant (p < 0.05) effect on the growth and yield parameters of maize. Maize plants that received basal fertilizer treatment at 4 WAP recorded the highest vegetative growth attributes while maize plants that received basal fertilizer treatment at 2 WAP produced the highest yield and yield components. The study concludes that the application of basal fertilizer at 2 WAP results in higher grain yield and yield components. It is therefore recommended that farmers apply basal fertilizer at 2 WAP to achieve optimum maize growth and grain yield.